Is the endogenous ligand for PEAR1 a proteoglycan: clues from the sea. (18th August 2021) - Kardeby, Caroline; Damaskinaki, Foteini-Nafsika; Sun, Yi; Watson, Stephen P.
Abstract: Platelet Endothelial Aggregation Receptor 1 (PEAR1) is an orphan receptor of unknown function which mediates powerful activation of platelets and endothelial cells in response to crosslinking by antibodies and sulfated polysaccharides belonging to the dextran and fucoidan families. PEAR1 is a single transmembrane protein composed of 15 epidermal growth factor-like repeat sequences and with a conserved binding motif, YXXM, which when phosphorylated binds to phosphoinositide 3-kinase (PI3K). The 13 th of the repeats has a heparin-binding sequence that is the site of interaction with the sulfated fucoidans and the only known endogenous ligand FcεRIα. Crosslinking of PEAR1 drives Src family kinase phosphorylation of the cytosolic tail leading to binding and activation of PI3K. In this Opinion Article, we summarize the literature on PEAR1 expression, structure and signaling, and the search for further endogenous ligands. We highlight one article in which phosphorylation of a 150 kDa platelet protein by heparin-containing ligands has been reported and propose that PEAR1 is a receptor for one or more glycosaminoglycan-conjugated proteins (proteoglycans). The up-regulation of PEAR1 at sites of inflammation in the vasculature and its role in angiogenesis suggests a role in the interplay of inflammation, platelets, coagulation, and thromboinflammation. We speculate that this may explain the link between single nucleotide variants in PEAR1 and cardiovascular disease.